2017
DOI: 10.1002/jcp.25925
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of prolactin inhibition of miR‐135b via methylation in goat mammary epithelial cells

Abstract: Prolactin is an important endocrine activator of lactogenesis. This study investigated the function and mechanism of miR-135b in the enhancement of lactation by prolactin in goat mammary epithelial tissue. We utilized S-Poly (T) sequencing to evaluate changes in gene regulation in the goat mammary gland after incubation with 2.5 μg/ml prolactin and 2.5 μg/ml IGF-1 by examining highly expressed miRNAs during early lactation and late-lactation. The results illustrated that miR-135b is highly expressed in the goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…Milk traits may be regulated by using DNA methylation and histone modification to interfere with the expression of galactolipid-related genes [41]. Chen et al 2018 [20] reported that PRL could regulate the expression of DNMT1 and affected the body function through the apparent modification, which is consistent with our results. PRL has a certain regulatory effect on genomic DNA methylation, but information on the regulation effect of PRL on breast fatty acids is still limited.…”
Section: Prl Regulates Mir-183 Expression By Methylation Regulationsupporting
confidence: 91%
See 1 more Smart Citation
“…Milk traits may be regulated by using DNA methylation and histone modification to interfere with the expression of galactolipid-related genes [41]. Chen et al 2018 [20] reported that PRL could regulate the expression of DNMT1 and affected the body function through the apparent modification, which is consistent with our results. PRL has a certain regulatory effect on genomic DNA methylation, but information on the regulation effect of PRL on breast fatty acids is still limited.…”
Section: Prl Regulates Mir-183 Expression By Methylation Regulationsupporting
confidence: 91%
“…Genomic DNA modified with bisulphite was used as the template, and BSP was used as a primer to amplify the methylated fragment of the miR-183 5 promoter. The PCR product was cloned into the pmd-19t vector, and the Top10 competent cells were transformed [20]. The mono-clones were collected and sent to Shanghai Yingjun Biotechnology Co., Ltd. for sequencing (Yingjun, Shanghai, China).…”
Section: Bisulphite Sequencing Pcr (Bsp) Of Mir-183mentioning
confidence: 99%
“…The RT‐qPCR assays were performed according to the manufacturer's instructions (SYBR Premix TaqMan®, Perfect Real Time) with the specific primers reported previously. Expression was normalized to that of GAPDH (Chen et al, ; Chen, Luo, et al, ). The primer sequences are listed in Table .…”
Section: Methodsmentioning
confidence: 99%
“…RNA samples complying with standardized criteria were used for subsequent experimentation. The full procedure is described in Chen et al (2018aChen et al ( , 2018b.…”
Section: Rna Extractionmentioning
confidence: 99%